From Foster Care to Enslavement: What Future for Africa’s Social Security System? - Henry Kam Kah (Modern Africa, 2015)
Foster care, an age-old tradition of social security in Africa has unfortunately been abused, bastardised and turned into an evil practice of enslavement with consequences for families, communities and countries. In different parts of the continent, this socio-cultural practice has been criticised by human rights groups; non-governmental organisations, competent government departments and religious groups and structures have been set up to educate parents and society about the evils associated with it. In spite of this, the practice has continued in different forms. This paper probes into the motivations for and evolution of this cultural practice. The practice was well intentioned in Africa’s past and resulted in the emergence of some elite or important personalities through fosterage. Unfortunately, this beneficial socio-cultural practice is now more or less an economic enterprise benefitting a network of government officials and other dubious individuals who pass for good Samaritans or pretend to fight it. From the look of things, the future of the practice spells greater enslavement if effective measures are not taken by relevant stakeholders to curb the excesses. The methodology in this study includes personal observation and discussion, discussion with children of foster parents, foster parents, and workers of NGOs dealing with such cases, church leaders, community leaders, newspaper reports and written texts.